Computational Analysis for Random Winglet Designs on Light Aircraft - Yadav, Ritesh; Kumar, Sachin; Lakshminarayana, Sanjay; Ratlamwala, Idris; Ratlamwala, Burhanuddin (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
This paper describes 3-dimensional wing-winglet analysis that was performed on random winglet designs on varying cross-sections of air foil. A total of four random wing-winglet pairs have been studied and their performance has been investigated according to their suitability on a light aircraft. The performance characteristics have been studied with CFD solver, static structural analysis for aluminum alloy material, when subjected to loads and moments experienced during turbulence and transient thermal analysis with initial temperature being 278 K and increasing up to 373 K. The heat flux at the first contact point of fluid-body interface is taken to be about 373 K; various simulation solutions have been developed. The angle of attack of the wing has been varied 0–15 degree with increments of 5, and lift to drag (L/D) ratio, drag coefficient have been found.